Preparação e caracterização de complexos de La3+, Ce3+, Pr3+, Nd3+, Sm3+ e Eu3+ com losartana - Santos, Anderson José dos (2020)
Inorganic chemistry has been important by the development and production of new coordination compounds used as drugs. The inorganic compounds are hammer out by organic ligands as amino acids, vitamins, and drugs. Among the drugs we have Losartan potassium (KLos), 2-butyl-4-chloro-1- [[2 '- (2H-tetrazole- 5-yl) [1,1'-biphenyl] -4-yl] methyl] - 1H-imidazole-5-methanol (C22H22ClKN6O), which has attractive properties for an analysis of new coordination compounds. In this work, losartan compounds with trivalent ions La3+, Ce3+, Pr3+, Nd3+, Sm3+ ,and Eu3+ obtained the solid-state. A close comparison with the FTIR spectra of the ligand, both theoretical and experimental, with synthesized compounds, suggested that their interaction with metal ions occurs through the tetrazole ring. Thermogravimetric analyzes provide information on the thermal stability of the synthesized compounds, degree of hydration, and stoichiometry: La(Los)3 .7H2O,Ce(Los)3.7H2O, Pr(Los)3.6H2O, Nd(Los)3.6H2O, Sm(Los )3.6H2O and Eu(Los)3.6H2O. XRD analyzes show that the formed compounds do not show crystallinity. As the analyzes of TG-DSC coupled to FTIR in the air atmosphere suggest the release of H2O, CO2, CO, MeOH, NH3, and -NCO during thermal decomposition of losartan from lanthanides.